Characterization and control of the laser micro soldering process for solid solder deposits using pyrometry - Pucher, Hans-Jörg; Fleckenstein, Marc (Proceedings of the Microelectronic Manufacturing Symposium 98, 1998)
Reflow soldering using laser beam radiation is an attractive joining technique for fine-pitch components used in electronics. It allows contactless and force-free processing of all optically accessible areas with limited and easily controllable heat supply. The analysis of pyrometer signals during laser micro soldering can be seen as the basis of process control. Therefore, the time-dependent courses of the thermal radiation of the joints during soldering were determined. They show characteristic arrests, turning points and changes in slope respectively. These changes permit a simplified classification of the soldering process in three phases: "reflow of the solder deposit", "wetting of the joining partners" and "cooling of the joint". In former research projects concerned with the characterization of the reflow behaviour and the wettability, only the actual solder deposit or the soldering of passive components were investigated. The tests were performed on fine-pitch structures made of FeNi42 and CuFe2P, typical materials used in electronics, and with solid solder deposits (SSD). The characteristic signal courses and the temperature of the joint were recorded with the aid of a PbSe pyrometer and with thermoelectric couples, the time of reflow was additionally determined by analyzing the structure-borne noise emission and the complete soldering process was visualized with a high-speed camera for the verification of the findings. The process windows were determined on the basis of optimum laser power and corresponding pulse duration. The use of pulse durations longer than e.g. 40 ms allowed clear recognition of characteristic features to be used a basis of control strategies (CuFe2P, pitch: 300 μm). Very short process durations (τH < 10 ms) could also realized with good soldering joints. However, control during this process is not possible because of the wetting process taking place with a time delay over the laser pulse. Also the process window, which lies between non-wetting and destruction of the joining partners, is very small.
LFT Import::2019-08-05 (1617)
Keywords: Cooling process; Laser micro soldering; Melting process; Process characterization; Pyrometry; Solid solder deposits (SSD); Wetting process